Family Decline and Lifestyle Change - Wang, Shiwei (Transactions on Social Science, Education and Humanities Research, 2024)
Family lifestyle is an important part of social lifestyle an important component of society’s way of life, throughout history, social change has always been linked to lifestyles, and changes in family lifestyles have reflected socio-economic development. Economic progression changed notions toward marriage in the recent years, and this has resulted in less fertility rate, and more children not living with both parents. Decline in marriage or split by parents can be treated as a shrinkage in family that can impose negative effect on overall level of education attainment and financial pressures.